1979
DOI: 10.1128/jb.137.1.384-390.1979
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of fatty acid biosynthesis by hydrocarbon substrates in Mycobacterium convolutum

Abstract: When Mycobacterium convolutum R22 was grown on the n-alkanes C13 through C16, the predominant fatty acids were of the same chain length as the growth substrate. Cells grown on C13 through C16 n-alkanes incorporated between 15 and 85 pmol of acetate per pg of lipid into the fatty acids, whereas acetate-or propanegrown cells incorporated 280 and 255 pmol of acetate per ,ug of lipid, respectively.In vivo experiments demonstrated that hexadecane, hexadecanoic acid, and hexadecanoylcoenzyme A (CoA) all inhibited de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1980
1980
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…The predominant fatty acids in n-hexadecane grown cells were C 16:0 (43.1 %), C 16:1 (25.4 %) and C 14:0 (11.8 %) obtained directly from the carbon skeleton of n-hexadecane. The obtained data correlate with the results of studying the cellular fatty acid composition of other representatives of hydrocarbon-oxidizing strains of actinobacteria, in particular Mycobacterium convolutum R22 [26] and Mycobacterium vaccae JOB5 [27], for which it has been demonstrated that the n-alkane substrate was incorporated into the cellular lipids after monoterminal oxidation. The presence in R. aetherivorans UCM Ac-602 cells a small amount of straight-chain unsaturated octadecenoic C 18:1 cis-9 fatty acid and a higher amounts of tetradecanoic C 14:0 , hexadecanoic C 16:0 and hexadecenoic C 16:1 cis-9 fatty acids, which were observed in n-hexadecane grown cells in comparison to those grown on glucose similar to the results obtained for the another strains of the genus Rhodococcus − Rhodococcus sp.…”
Section: Discussion Actinobacteria Of the Genussupporting
confidence: 83%
“…The predominant fatty acids in n-hexadecane grown cells were C 16:0 (43.1 %), C 16:1 (25.4 %) and C 14:0 (11.8 %) obtained directly from the carbon skeleton of n-hexadecane. The obtained data correlate with the results of studying the cellular fatty acid composition of other representatives of hydrocarbon-oxidizing strains of actinobacteria, in particular Mycobacterium convolutum R22 [26] and Mycobacterium vaccae JOB5 [27], for which it has been demonstrated that the n-alkane substrate was incorporated into the cellular lipids after monoterminal oxidation. The presence in R. aetherivorans UCM Ac-602 cells a small amount of straight-chain unsaturated octadecenoic C 18:1 cis-9 fatty acid and a higher amounts of tetradecanoic C 14:0 , hexadecanoic C 16:0 and hexadecenoic C 16:1 cis-9 fatty acids, which were observed in n-hexadecane grown cells in comparison to those grown on glucose similar to the results obtained for the another strains of the genus Rhodococcus − Rhodococcus sp.…”
Section: Discussion Actinobacteria Of the Genussupporting
confidence: 83%
“…We used radioisotope tracing to test whether PYRC and EQI would inhibit incorporation of acetate into fatty acids of treated S. aureus. Radiolabeled acetate is a well-established tool to trace de novo fatty acid synthesis [22][23][24]. Upon entering the cell, acetate is converted into acetyl-CoA by acetyl-CoA synthase and utilized by subsequent pathways, including fatty acid biosynthesis.…”
Section: Pyrc and Eqi Inhibit De Novo Fatty Acid Synthesis In S Aureusmentioning
confidence: 99%
“…As the initial step in utilization of alkanes, a coenzyme A-independent internal cis-desaturation may be involved, where an unsaturated metabolite generated would be then split at the double bond into two shorter chain FAs and ultimately oxidized via ␤-oxidation. This postulated pathway is different from the wellknown subterminal oxidation system that converts alkanes initially to their alkyl alcohols and then to FAs, which are further degraded by a ␤-oxidation system (13), as in yeast (2) and other microorganisms (1). The hyperproduction of unsaturated products by mutant KSM-B-3M suggests that the mutation might occur on the gene encoding a double bond-splitting enzyme, since the mutant strain grows poorly on n-hexadecane but well on FA16, and converts aliphatic substrates mainly to cis-9-unsaturated products having the same chain length.…”
mentioning
confidence: 91%